Direct water requirement patterns in Brazil, Colombia and Costa Rica: A structural decomposition analysis - Giovanna Ferrazzo Naspolini; Jesse Libra; Santiago Cunial; María Pérez-Urdiales (Inter-American Development Bank (IDB), 2024)
Water is not only vital for human life but also is a critical economic input. Climate change will likely exacerbate conflicts over the multiple uses of water in Latin America. Adopting a south-south perspective approach, this study compares direct water requirement patterns over time among Brazil, Colombia, and Costa Rica, applying an environmental-extended Structural Decomposition Analysis between 2013 and 2017. While all countries experienced increased water consumption during the period, Brazils and Colombias results suggest gains in water productivity at the national level and for Agriculture. Results also indicate that Exports are the main water consumption driver of Agriculture in Brazil and Costa Rica. The Water and sanitation sector in Colombia experienced a decrease in direct water requirements, which is illustrated by a strong negative intensity effect. In contrast, an expressive positive intensity effect in Costa Rica resulted from a sectoral GDP fall. The findings of this study offer support to sectoral climate adaptation plans in all countries as well as water conservation and sustainable development policies.
Keywords: Q25; Q56; R15; 330; input-output tables; sustainable development; water footprint